"Review of Mormon Feminism: Essential Writings - Annus, Iren (AMERICANA E-journal of American Studies in Hungary, 2018)
Mormon Feminism: Essential Writings Eds. Joanna Brooks, Rachel Hunt Steenblik and Hannah Wheelwright New York: Oxford University Press, 2016. 324 pages ISBN (13): 978-0-19-024803-1 (Hardcover) ISBN (13): 978-0-19-084838-5 (Paperback)